Buccal mucosa graft urethroplasty in a case of urethral amyloidosis presenting with long anterior urethral stricture - Kurbatov, Dmitry (Can Urol Assoc J, 2015)
Urethral amyloidosis is a rare condition, but clinically relevant because it can mimic urothelial carcinoma. We report a case of localized urethral amyloidosis presenting with a long anterior urethral stricture. We used extensive grafts of buccal mucosa for standard augmentation urethroplasty, with a successful outcome at the 2-year follow-up.